Sleep Disorders and Reproductive Health: Mechanisms, Consequences, and Potential Interventions - Magdalena Rosa-Bończak Rosa; Patrycja Marta; Filip Maciej Huzarski; Klaudia Anna Pawełek; Gabriela Monika Ferfecka; Agata Ossolińska; Natalia Morawiecka; Lucyna Stolarska; Oliver Carlton; Weronika Kłosowicz (Journal of Education, Health and Sport)
Introduction